Answer:
Option B. 3 m/s east
Step-by-step explanation:
From the question given above, the following data were obtained:
Initial velocity (u) = 2 m/s east
Final velocity (v) = 5 m/s east
Time (t) = 6 s
Change in velocity =?
We can obtain the change in Lee's velocity as illustrated below:
Initial velocity (u) = 2 m/s east
Final velocity (v) = 5 m/s east
Change in velocity =?
Change in velocity = Final velocity (v) – Initial velocity (u)
Change in velocity = v – u
Change in velocity = 5 – 2
Change in velocity = 3 m/s east
Thus, the change in Lee's velocity is 3 m/s east